Developing research based learning to increase students’ entrepreneurial interest - Zelhendri Zen; Johari bin Sihes; Reflianto (Fakultas Ilmu Pendidikan UNP)
The aim of research was to develop research-based learning models to increase students’ entrepreneurial interest in State University of Padang. It was begun by doing the related surveys for current situation of entrepreneurial teachingdid not provide yetthe knowledge and students’ entrepreneurial expectations. For that reason need a research-based learning to empower student’s strategy in the field of real business as well as to improve students’ self-evaluation in enhancing their ability to take the business opportunity as the manifestation of the entrepreneurship course. This research used research and development method with Triangulation Mixed Method Design. Updating of the models was done by doing the curriculum assessment with specialists and practitioners. The collection of the data used questionnaires, interviews, documentary studies, training and mentoring as well as Focus Group Discussion (FGD). Quantitative data were analyzed by using an experimental model by using independent t-test. The experimental results on the three classes showed that research-based learning models can give positive impact to students’ entrepreneurial interest and this model had qualified and allowable to be used as teaching materials for entrepreneurship courses at the Education Faculty of State University of Padang.The developed model was expected become a feasible choice by entrepreneurshiplecturers to the implementation of entrepreneurship course for university students at faculty of Education in State University of Padang.